Investment Priorities in Central and Eastern Europe With A Hint of Software Manufacturer’s Perspective - Ihor HURNYAK; Arkadiusz NIEDZWIECKI; Marek PRONIEWSKI (Communications of International Proceedings, 2022)
The stock markets of Central and Eastern Europe (CEE) predictably are not as efficient as the markets of developed countries. This fact has been revealed even more obvious and painful in time of pandemic. If the markets of developed countries during the pandemic show a clear commitment to the telecommunication, Internet services (study), software, automation, robotics, etc., the allegiances of stock markets in the CEE is not so clear, in particular, due to the institutional imperfection of its still transforming mechanism. But as expected the study based on a portfolio of leading companies from the Czech Republic, Poland and Hungary revealed close partly hidden trends. The experience of the described IT, business and financial service companies proves similar to the developed markets investment priorities in favor of technological business showing the clear advantages of its work on the stock markets and indicating long-term trend of investor confidence. A comparison is made with the portfolio of representatives of the index DAX in Germany. The revealed commitment to mobility and market diversification has been proposed as very promising for CEE public issuers.
Keywords: stock market; pandemic influence; Sharpe ratio; portfolio optimization; information technologies